School Leaders’ Perceptions, Practices and Aspirations About Schoolification in Ecec - Galdames-Poblete, S (SAGE Publications Inc., 2025)
This paper explores school leaders’ perspectives on Early Childhood Education and Care (ECEC) schoolification and how they tackle this trend, drawing upon literature on leadership in both the ECEC context and the school system. Through a qualitative framework, 10 Chilean leaders from five publicly funded K-12 (kindergarten to Grade 12) schools – principals and instructional coordinators – were interviewed. Findings show that school leaders know little about ECEC, significantly moderating their possibilities to work with this educational level. When addressing the schoolification phenomenon, our data indicate that while school leaders care about it, particularly about the negative consequences for children, they have few skills and tools to support the work of ECEC teachers. Even though leaders have promoted some measures to tackle ECEC schoolification in the schools they lead, we argue that these strategies tend to be aspirational or sporadic rather than systematic and long-term. These findings contribute to understanding how school leaders shape ECEC practices, highlighting the need for the development of leadership to effectively address schoolification. © The Author(s) 2025. This article is distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 License (https://creativecommons.org/licenses/by-nc/4.0/) which permits non-commercial use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access page (https://us.sagepub.com/en-us/nam/open-access-at-sage).